The Focus of Supervisor Written Feedback to Thesis/Dissertation Students - Bitchener, John; Basturkmen, Helen; East, Martin (International Journal of English Studies, 2010)
Written feedback on drafts of a thesis or dissertation is arguably the most important source of input on what is required or expected of thesis-writing students by the academic community. Despite its importance, relatively little is known about what type of information supervisors focus on when giving feedback. This article presents the findings of an exploratory, descriptive study that investigated what supervisors said they focused on when giving feedback. A total of 35 supervisors across three disciplines (Humanities, Sciences/ Mathematics, Commerce) at six New Zealand universities participated in the study. Data were sought from self –report data (written questionnaires and interviews) and samples of feedback given on thesis drafts. The study found that a wide range of beliefs concerning feedback are held by supervisors, that there is little difference in the type of feedback provided by supervisors in the different disciplines and that similar feedback tends to be given to both L1 and L2 students.